The Dynamics of Rice Farmer Empowerment and an Evaluation of the Readsi Program (Rural Empowerment and Agriculture Development Scaling-Up Initiative) - Maulana, Alfian Akmal; Suryanto, Suryanto; Akmal, Akmal (Riwayat: Educational Journal of History and Humanities, 2025)
With the decentralization of governmental authority in the implementation of regional autonomy, it is expected that the application of the concept of good governance in government administration, development, and public service can be realized, including in the field of education. The method used in this research is a literature study. The data used in this research are primary data sourced from various research reports and journals, as well as secondary data sourced from various books and legislation. The results of the research show that through the concept of educational decentralization, educational management is able to shift from a top-down to a participatory bottom-up management pattern. As a result, management develops and organizes educational administration in a comprehensive and integrated manner. Educational institutions, as the organizers of education, build networks and develop communication and cooperation with various elements, including the government, society, and the private sector. Through the concept of educational decentralization, schools are able to design school policies according to the schools vision and integrate them with their environment, both the social community and the natural environment.